2000
DOI: 10.1046/j.1440-1770.2000.00115.x
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of Cylindrospermopsis raciborskii (Nostocales, Cyanoprokaryota) in Queensland tropical and subtropical reservoirs: Implications for monitoring and management

Abstract: Since October 1997, 47 reservoirs and weir pools across tropical and subtropical Queensland have been regularly monitored for the occurrence of planktic cyanoprokaryotes. Cylindrospermopsis raciborskii (Woloszynska) Seenaya & Subba Raju (Nostocales, Cyanoprokaryota) was found in 70% of the storages, with one storage displaying year‐round dominance, 50% of the reservoirs seasonally dominated and a seasonal presence in 46% of the weir pools. Maxima for the majority of storages occurred from late summer through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
113
2
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(130 citation statements)
references
References 32 publications
11
113
2
4
Order By: Relevance
“…The first confirmed identification of this species in New Zealand was by Wood & Stirling (2003) in Lake Waahi in March 2003. There is considerable morphological variation in C. raciborskii (McGregor & Fabbro 2000) and this is one of the reasons for its recent appearance in water bodies where it has been previously unrecorded. A morphologically similar species, Cylindrospermum minutissimum Collins, has previously been described in lakes in close proximity to our study lakes (Etheredge & Pridmore 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first confirmed identification of this species in New Zealand was by Wood & Stirling (2003) in Lake Waahi in March 2003. There is considerable morphological variation in C. raciborskii (McGregor & Fabbro 2000) and this is one of the reasons for its recent appearance in water bodies where it has been previously unrecorded. A morphologically similar species, Cylindrospermum minutissimum Collins, has previously been described in lakes in close proximity to our study lakes (Etheredge & Pridmore 1987).…”
Section: Introductionmentioning
confidence: 99%
“…The identification was based upon earlier keys, and the emphasis on the position of the heterocyst being adjacent to the akinete led to material being identified as C. minutissimum, while the absence of heterocysts and tapering of trichomes led to identifications of the material as Raphidiopsis; both of these forms are described in the New Zealand literature. Correct identification of Cylindrospermopsis raciborskii is very difficult, due in part to the large range of morphological variants which have been documented in recent taxonomic investigations (McGregor & Fabbro 2000) and using genetic studies Wilson et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, distinction between these two genera is difficult when heterocytes are not shown in Cylindrospermopsis strains (Li et al, 2001;Moustaka-Gouni et al, 2009;Alster et al, 2010). The coexistance of Cylindrospermopsis and Raphidiopsis in the same waters has been widely reported (McGregor and Fabbro, 2000;Moustaka-Gouni et al, 2009;Wu et al, 2011). Raphidiopsis-like trichomes are regarded as only environmental types of Cylindrospermopsis (McGregor and Fabbro, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…They share similar ecological niches, in which Raphidiopsis species have been found to co-occur with Cylindrospermopsis raciborskii (Woloszyń ska) Seenayya et Subba Raju in a range of waters (Moustaka-Gouni et al, 2009;Wu et al, 2011;Hill, 1970). McGregor and Fabbro (2000) proposed that Raphidiopsis-like trichomes are only environmental morphotypes and the heterocyst-omission phase of C. raciborskii. Moustaka-Gouni et al (2009) suggested that Raphidiopsis mediterranea Skuja represents nonheterocytous life-cycle stages of C. raciborskii in Lake Kastoria (its type locality), Greece, as evidenced by morphological and 16S rRNA phylogenetic analyses.…”
Section: Introductionmentioning
confidence: 99%
“…However, blooms are complex events, involving multiple environmental factors simultaneously (Heisler et al, 2008), which have led to some inconsistencies in the literature, related to the environmental parameters tested (Posselt et al, 2009). The main shortcoming is that many studies have provided specific information about the environmental requirements of the two species occurring separately (McGregor and Fabbro, 2000), while very few of them have recently reported the co-occurrence of C. raciborskii and P. agardhii in lakes and reservoirs (Stefaniak and Kokocinski, 2005;Kokocinski et al, 2009). For example, in the Tunisian Bir M'Cherga reservoir, from which the strains used in this study were obtained, P. agardhii occurs as a perennial biomass and dominates the phytoplankton community, whereas C. raciborskii is favored by higher temperatures and light intensities that only occur for a short period each year (Jenhani et al, 2012).…”
Section: Introductionmentioning
confidence: 99%